2006
DOI: 10.1111/j.1398-9995.2006.01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells express IL‐13Rα1: IL‐13 promotes human lung mast cell proliferation and FcɛRI expression

Abstract: Human lung mast cell express IL-13Ralpha1 and activation by IL-13 for 5 days increased FcepsilonRI expression and proliferation. Histamine release was not affected by short-term priming with IL-13, but was upregulated by priming for 5 days suggesting that this effect was mediated by the increased FcepsilonRI expression. These data support the view that targeting IL-13 may be beneficial in the treatment of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 32 publications
0
64
0
Order By: Relevance
“…Early therapeutic potential of CAT-354 for asthma was demonstrated by Blanchard et al via a murine model in which CAT-354 significantly inhibited IL-13-induced AHR and airway eosinophilia [14]. Kaur et al demonstrated that human lung mast cells (HLMCs) expressed IL-13, that IL-13 can up-regulate allergic functions of HLMCs and, specifically, that CAT-354 inhibited all of these IL-13-mediated effects in HLMCs [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early therapeutic potential of CAT-354 for asthma was demonstrated by Blanchard et al via a murine model in which CAT-354 significantly inhibited IL-13-induced AHR and airway eosinophilia [14]. Kaur et al demonstrated that human lung mast cells (HLMCs) expressed IL-13, that IL-13 can up-regulate allergic functions of HLMCs and, specifically, that CAT-354 inhibited all of these IL-13-mediated effects in HLMCs [15].…”
Section: Discussionmentioning
confidence: 99%
“…CAT-354 is a human monoclonal IgG4 antibody which has been shown to neutralize IL-13 in both the murine airway [14] and human lung mast cells [15]. Phase 1 data in subjects with mild-to-moderate asthma have demonstrated safety and tolerability profiles that support continued clinical development of CAT-354 [16].…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] IL-13 is also known to promote mast cell proliferation. 16,26 IL-13 is produced by Th2 lymphocytes and activated mast cells and is implicated in the immunopathogenesis of various allergic diseases. 16,26,27 The relationship between mast cell infiltration and the histological subtype of CHL (NSCHL or non-NSCHL) remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…12 Mast cell proliferation is induced by IL-3, IL-13, and stem cell factor (SCF). [13][14][15][16] We investigated the association of fibrosis in lymph nodes (LNs) of patients with CHL through histological examination of the expression of cytokines associated with fibrosis and mast cell proliferation (TGF-β, IL-3, IL-13, and SCF) and by determining the degree of mast cell infiltration in NSCHL compared with that in non-NSCHL (MCCHL or LRCHL).…”
Section: Introductionmentioning
confidence: 99%
“…The accumulated data have led to the conclusion that IL13R␣2 functions in most cell types as a critical decoy/inhibitory receptor for IL-13-dependent activation of cells. Kaur and coworkers (56) showed that in vivo-differentiated MCs from human lung also express IL13R␣1, and Lorentz and coworkers (57) showed that normal human intestinal MCs express both IL13R␣1 and IL13R␣2. Not only do canine MC lines express IL13R␣1 and IL13R␣2, the transcript that encodes canine IL13R␣2 was first cloned from a mastocytoma cell line (58).…”
Section: Discussionmentioning
confidence: 99%